2013
DOI: 10.1186/1755-7682-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different protocols of hydration on cardiorespiratory parameters during exercise and recovery

Abstract: IntroductionHydration plays a key role in the physiological maintenance required by exercise.ObjectiveTo evaluate the behavior of heart rate (HR), systolic (SBP) and diastolic (DBP) blood pressure, pulse oxygen saturation (SpO2) and respiratory rate (RR) of young people during and after prolonged physical exercise, with and without the intake of water or isotonic solution.Method31 young individuals (21.63 ± 1.86 years) were subjected to a four-step protocol with a 48-hour interval between each step, namely: i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…The authors observed lower oxygen saturation levels and higher HR during recovery on control visits compared with those involving water or isotonic intake, and no protocols demonstrated an effect on blood pressure or respiratory rate. These studies [43,45] are consistent with the results of the present study, in which higher CVI values during recovery were obtained after 500 ml of water intake compared with 50 ml. Although our study was not aimed at verifying the physiological mechanisms of the effects of drinking on cardiac autonomic reactivation, based on other studies, it can be speculated that the observed effect may be related to either gastrovascular reflex (gastric distention) [39,44] or osmotic factors [13,29].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The authors observed lower oxygen saturation levels and higher HR during recovery on control visits compared with those involving water or isotonic intake, and no protocols demonstrated an effect on blood pressure or respiratory rate. These studies [43,45] are consistent with the results of the present study, in which higher CVI values during recovery were obtained after 500 ml of water intake compared with 50 ml. Although our study was not aimed at verifying the physiological mechanisms of the effects of drinking on cardiac autonomic reactivation, based on other studies, it can be speculated that the observed effect may be related to either gastrovascular reflex (gastric distention) [39,44] or osmotic factors [13,29].…”
supporting
confidence: 92%
“…Drinking water has been shown to induce cardiovascular and autonomic responses [6,14,25,40]. Previous studies found that hydration accelerates post-exercise cardiovascular recovery after a single session of submaximal aerobic exercise [43,45]. Vianna et al [45] reported that drinking 500 ml of water immediately after 30 min of cycling exercise at a workload representing 80 % of anaerobic threshold accelerated post-exercise cardiac vagal reactivation in 10 healthy subjects, suggesting that hydration after aerobic exercise may be an effective strategy for increasing postexercise cardiovascular safety.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, different strategies to accelerate the autonomic and cardiovascular system recovery after physical exercise practice have been studied on literature [15][16][17][18][19][20] , and water intake is one of than [21][22][23] . Studies that investi-gated the effects of water intake associated to physical exercise, pointed that this strategy was able to attenuate cardiovascular 18,24 and autonomic [20][21][22][23] alterations promoted by the thermic stress as a result of physical exercise and to promote a faster recovery of the organism 18,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%